DIGITAL LITERACY AND LEARNING MOTIVATION: A QUALITATIVE EXPLORATION OF THEIR IMPACT ON WRITING ABILITIES - Puspitasari, Ema; Rusmalinda, Riski (As-Sulthan Journal of Education, 2025)
This qualitative study explores the interplay between digital literacy and learning motivation in shaping students’ academic writing abilities within an Islamic higher education context. Guided by three research aims, it investigates how students describe the role of digital literacy in their writing processes, how learning motivation influences their writing behaviors, and how both factors interact in their writing development. Data were collected through semi-structured interviews and document analysis, enabling the capture of students’ voices and personal narratives. Findings reveal that digital literacy supports efficient research, idea organization, and editing skills, while learning motivation sustains persistence and goal orientation in writing tasks. The interaction between these factors fosters both technical competence and value-driven writing practices rooted in Islamic principles. This study offers practical insights for curriculum design, pedagogical strategies, and institutional policies aimed at empowering students to write with confidence, purpose, and integrity.